First report of molecular diagnosis of Tunisian hemophiliacs A: Identification of 8 novel causative mutations - Elmahmoudi Hejer; Khodjet-; Wigren Edvard; Jlizi Asma; Zahra Kaouther; Pellechia Dorothé; Vinciguerra Christine; Meddeb Balkis; Elggaaied Amel Ben; Gouider Emna (BMC, 2012)
Abstract Introduction Hemophilia A is an X linked recessive hemorrhagic disorder caused by mutations in the F8 gene that lead to qualitative and/or quantitative deficiencies of coagulation factor VIII (FVIII). Molecular diagnosis of hemophilia A is challenging because of the high number of different causative mutations that are distributed throughout the large F8 gene. Molecular studies of these mutations are essential in order to reinforce our understanding of their pathogenic effect responsible for the disorder. Aim In this study we have performed molecular analysis of 28 Tunisian hemophilia A patients and analyzed the F8 mutation spectrum. Methods We screened the presence of intron 22 and intron 1 inversion in severe hemophilia A patients by southern blotting and polymerase chain reaction (PCR). Detection of point mutations was performed by dHPLC/sequencing of the coding F8 gene region. We predict the potential functional consequences of novel missense mutations with bioinformatics approaches and mapping of their spatial positions on the available FVIII 3D structure. Results We identified 23 different mutations in 28 Tunisian hemophilia A patients belonging to 22 unrelated families. The identified mutations included 5 intron 22 inversions, 7 insertions, 4 deletions and 7 substitutions. In total 18 point mutations were identified, of which 9 are located in exon 14, the most mutated exonic sequence in the F8 gene. Among the 23 mutations, 8 are novel and not deposited in the HAMSTeRS database nor described in recently published articles. Conclusion The mutation spectrum of Tunisian hemophilia A patients is heterogeneous with the presence of some characteristic features. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1693269827490715